2022
DOI: 10.3926/jiem.4168
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy-based product substitution design rationale: A case of personal care product

Abstract: Purpose: This study describes an empirical study demonstrating the application of circular economy (CE) to respond to an urgent call to reduce plastic waste by utilizing waste from the furniture industry.Design/methodology/approach: this study employed the measurements of environmental impacts of plastic and wood-based toothbrushes using a life cycle assessment, complemented by an analysis of the wood substitution design process from a CE perspective.Findings: The findings from this study not only shed light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Eco-efficiency is a strategy that combines economic and ecological efficiency principles in the utilization of natural resources [22,11]. The formula for calculating the Eco-efficiency Index (EEI) involves dividing the net value by the eco-cost, where the net value is determined as the selling price minus the cost.…”
Section: Eco-efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Eco-efficiency is a strategy that combines economic and ecological efficiency principles in the utilization of natural resources [22,11]. The formula for calculating the Eco-efficiency Index (EEI) involves dividing the net value by the eco-cost, where the net value is determined as the selling price minus the cost.…”
Section: Eco-efficiencymentioning
confidence: 99%
“…Utilizing rice husk fuel for briquette production aligns with the principles of a circular economy [8]. Various studies have shown the economic, environmental, and social benefits of recycling waste as an alternative to harmful materials [9][10][11].…”
Section: Introductionmentioning
confidence: 99%